The Effect of Income, Locus of Control on Financial Management Behavior of K-Popers Community Members in Pekanbaru City with Hedonism Lifestyle as a Moderating Variable - Selfia, Lia; Rokhmawati, Andewi; Rahmayanti, Elvi (Program Pascasarjana, Universitas Riau, 2024)
This study aims to examine the effect of income and locus of control on financial management behavior of K-Popers community members in Pekanbaru city with hedonism lifestyle as a moderating variable. The population in this study included K-Pop fans in Pekanbaru city who fit certain criteria with a sample of 330 respondents. The sampling technique was purposive sampling. Data analysis using structural equating modeling on partial least square. The results showed that income has a positive and significant effect on the financial management behavior of K-Popers community members in Pekanbaru city. Locus of control has a positive and significant effect on the financial management behavior of K-Popers community members in Pekanbaru city. Hedonism lifestyle has a significant negative effect on the financial management behavior of K-Popers community members in Pekanbaru city. Hedonism lifestyle as a moderating variable weakens the positive relationship between income and financial management behavior of K-Popers community members in Pekanbaru city and is significant. While hedonism lifestyle as a moderating variable weakens the positive relationship between locus of control and financial management behavior of K-Popers community members in Pekanbaru city but is not significant